Syndromic Retinitis Pigmentosa A Narrative Review - Janáky Márta; Braunitzer Gábor (2025)
Retinitis pigmentosa (RP) encompasses inherited retinal dystrophies, appearing either as an isolated eye condition or as part of a broader systemic syndrome, known as syndromic RP. In these cases, RP includes systemic symptoms impacting other organs, complicating diagnosis and management. This review highlights key systemic syndromes linked with RP, such as Usher, Bardet–Biedl, and Alström syndromes, focusing on genetic mutations, inheritance, and clinical symptoms. These insights support clinicians in recognizing syndromic RP early. Ocular signs like nystagmus and congenital cataracts may indicate systemic disease, prompting genetic testing. Conversely, systemic symptoms may necessitate eye exams, even if vision symptoms are absent. Understanding the systemic aspects of these syndromes emphasizes the need for multidisciplinary collaboration among ophthalmologists, pediatricians, and other specialists to optimize patient care. The review also addresses emerging genetic therapies aimed at both visual and systemic symptoms, though more extensive studies are required to confirm their effectiveness. Overall, by detailing the genetic and clinical profiles of syndromic RP, this review seeks to aid healthcare professionals in diagnosing and managing these complex conditions more effectively, enhancing patient outcomes through timely, specialized intervention.
Keywords: Általános orvostudomány